Altered levels of IFN-γ, IL-4, and IL-5 depend on the TLR4 rs4986790 genotype in COPD smokers but not those exposed to biomass-burning smoke - Gutiérrez-Romero, Karla Jazmín; Falfán-Valencia, Ramcés; Ramírez-Venegas, Alejandra; Hernández-Zenteno, Rafael De Jesus; Flores-Trujillo, Fernando; Sansores-Martínez, Raúl; Ramos-Martínez, Espiridión; Pérez-Rubio, Gloria (Frontiers in Immunology, 2024)
Introduction Chronic obstructive pulmonary disease (COPD) is associated with tobacco smoking and biomass-burning smoke exposure. Toll-like receptor 4 (TLR4) single-nucleotide polymorphisms (SNPs) may contribute to its pathogenesis. The study aimed to assess the association of rs4986790 and rs4986791 in the TLR4 gene in a Mexican mestizo population with COPD secondary to tobacco smoking (COPD-TS) and biomass-burning smoke (COPD-BBS) and to evaluate whether the genotypes of risk affect cytokine serum levels. Materials and methods We enrolled 2,092 participants and divided them into two comparisons according to their environmental exposure. SNPs were genotyped using TaqMan probes. Serum cytokine levels (IL-4, IL-5, IL-6, IL-10, and INF-γ) were quantified by ELISA. Results The rs4986790 AA genotype in COPD-TS was associated with a higher COPD risk (OR = 3.53). Haplotype analysis confirmed this association, identifying a block containing the rs4986790 allele (A–C, OR = 3.11). COPD-TS exhibited elevated IL-6, IL-4, and IL-5 levels compared with smokers without COPD (SWOC), whereas COPD-BBS displayed higher IFN-γ, IL-6, and IL-10 levels. The AA carriers in the COPD-TS group had elevated IL-4, IL-5, and IFN-γ compared with carriers of AG or GG. Conclusion The rs4986790 common allele and the A–C haplotype (rs4986790–rs4986791) were associated with a higher COPD risk in smokers; COPD patients carrying the AA genotype showed increased pro-inflammatory cytokines.